2018
DOI: 10.18805/bkap120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop regulation practices on yield and economics in Guava (Psidium gjajava L.) fruit crop

Abstract: An experiment on the effect of crop regulation practices on Guava fruit crops was conducted during 2016-17 and 2017-18. The results revealed maximumand statistically higher yield (119.73 q/ha.), gross return (Rs 32925 per hectare) and Net return (Rs230529 per hectare) under application of 800 PPM NAA plant growth regulator. Highest cost benefit ratio (1:3.33) was also recorded under the treatment of 800 ppm of NAA which was most economic and feasible practice of crop regulation in guava fruit crop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The application of auxins caused translocation of hormones, food substances and other factors stimulating fruit formation to the tissues of ovary in greater amount which resulted in higher fruit set [9]. Similar results are reported by Gurjar [10], Dhillon et al [11] Agnihotri et al [12], Brar et al [13] Jain and Dashora [14], Singh and Dhaliwal [15], and Pandey et al [16].…”
Section: Percent Fruit Setmentioning
confidence: 57%
See 1 more Smart Citation
“…The application of auxins caused translocation of hormones, food substances and other factors stimulating fruit formation to the tissues of ovary in greater amount which resulted in higher fruit set [9]. Similar results are reported by Gurjar [10], Dhillon et al [11] Agnihotri et al [12], Brar et al [13] Jain and Dashora [14], Singh and Dhaliwal [15], and Pandey et al [16].…”
Section: Percent Fruit Setmentioning
confidence: 57%
“…The similar observation was also reported by Desai et al [19], Choudhary et al [23], Dubey et al [24], Nanra et al [25], Das et al [20], Singh et al . [26] Sahar and Hameed [27], Rajput et al [28], Agnihotri et al [12], Singh [29], Dhillon et al [11], Gurjar [10] and Bashir et al [22] by regulating rainy season crop. Similarly, Shankar et al [30][31] reported that the maximum fruit yield per plant was recorded with control during the rainy season.…”
Section: Fruit Yield Per Plant (Kg/tree)mentioning
confidence: 99%
“…Understanding of crop regulation will help to optimize harvest time which reduce surplus in the market, to obtain higher price of the produce, to avoid spoilage due to excessive production at a particular time, to provide employment throughout the year and balance the trade and to reduce imports. Gurjar et al, (2018) obtained maximum and statistically higher yield (119.73 q/ ha. ), gross return (Rs 32925 per hectare) and net return (Rs 230529 per hectare) under application of 800 PPM NAA plant growth regulator.…”
Section: Crop Regulation For Economic Benefitsmentioning
confidence: 90%
“…According to research, maximum and statistically higher yield (119.73 q/ha), gross return (Rs. 32925 per hectare) and net return (Rs 230529 per hectare) as well as cost benefit ratio (1:3.33) were obtained under the application of 800 PPM NAA plant growth regulator [58]. Similarly, it was reported that a significantly higher yield (100 kg/tree) was found in Allahabad Safeda with the spray of 10% urea during the winter season, while Sardar guava recorded the highest yield (103.98 kg/tree) with the spray of 1800 ppm ethephon during the same season which was closely followed by 20 and 15% urea (100.25 and 96.38 kg/tree, respectively) [10].…”
Section: Crop Regulation For Economic Benefitsmentioning
confidence: 98%